The Supporting “I”: Otherness and Doubles in Contemporary Scottish Literature - Viktoriia Ivanenko (Pitannâ Lìteraturoznavstva, 2017)
The paper studies the ways supporting characters function in contemporary Scottish prose. “Supportiveness” is interpreted in the context of “Caledonian Antisyzygy”, a term offered by George Gregory Smith in his Scottish Literature: Character and Influence (1919). As Belfast-based scholar claims, “Perhaps in the very combination of opposites […] we have a reflection of the contrasts which Scot shows at every turn, in his political and ecclesiastical history, in his polemical restlessness, in his adaptability, which is another way of saying that he has made allowance for new conditions, in his practical judgment, which is the admission that two sides of the matter have been considered. If therefore Scottish history and life are, as an old northern writer said of something else, “varied with a clean contrair spirit”, we need not be surprised to find literature the Scot presents two aspects which appear contradictory”. Thus, supporting characters are seen through “contrair spirit” and the tradition of combining the opposites. The paper also studies the major functions that the supporting character performs in A. L. Kennedy, James Robertson, Irvine Welsh, and Iain Banks’ fictions. Technically, in contemporary Scottish prose supporting characters construct the major ones mainly in two ways: first, they perform the role of the deferred Other who identifies the protagonist in the process of difference, i. e. the one actually becoming the other. Second, supporting characters mirror, double, or echo the major ones not only to construct the protagonist’s psychological projections, desires, or fears, but also to create a specifically Scottish atmosphere where the line between the real and the fictional, the natural and the supernatural is blurred, and “whaur extremes meet”.